CALCULATION OF EMISSIONS FROM TRANSPORT SERVICES AND THEIR USE FOR THE INTERNALISATION OF EXTERNAL COSTS IN ROAD TRANSPORT (Perner's Contacts, 2016)
Impact of transport operations on the environment is an important criterion of quality services. Requirements for environmental acceptability has recently escalated, manufacturing and trading companies require the carriers to declare the impact of their activities on the environment. Area of concern are the emission factors used for calculating emissions and their unification. For this reason it was accepted norm STN EN 16258, which deals with the methodology of calculation and declaration of energy consumption and greenhouse gas emissions from transport services. Existing emission calculators do not allow the calculation of the external costs of transport services in the area of transport services impacts on the environment. Article deals with the design and application of the calculator of external costs of transport services as an extension, respectively another important function, emission calculator for field of transport services.
Keywords: emissions; road transport; transport service; external costs; internalisation